Systematics and biogeography of Cuban porcelain crabs (Decapoda: Anomura: Porcellanidae) - Diez, Yander L.; Lira, Carlos (Zootaxa, 2017)
Marine crustaceans are a well-known invertebrates group in Cuban waters, but some taxa are not well catalogued and the literature about them is scattered. In this work, we present the checklist of porcelain crabs of Cuban Archipelago, including the literature registers and unpublished author’s data. A key to the identification of 8 genera and 23 species of the Cuban porcelain crabs is provided. Information about the local distribution of species is presented. In addition, we analyzed the porcelain crab faunal affinities between the ecoregions of the Cuban platform, Greater Antilles islands and the Tropical Northwestern Atlantic (TNA) province. For the first time, we record the presence of the monotypic genus Parapetrolisthes Haig in Cuba. On the Cuban platform, the highest similarities are between the Southcentral and Northwestern ecoregions (50%) and between Northcentral and Northeastern (40%). In the Greater Antilles, Cuba and Puerto Rico are the most similar (54%), but in general, the porcelain crab composition shows a high variation (e. g. 19% between Hispaniola and Puerto Rico). In the Tropical Northwestern Atlantic, five homogeneous groups of porcelain crab species are distinguished. Cuban fauna is most similar to that of Floridian, Western Caribbean and Southern Gulf of Mexico ecoregions. The decrease in species richness is evident from south to north in the TNA Province.